BASIC DESIGN OF OUTPUT WITH MEDIATOR programmable PERIPHERAL INTERFACE USING LANGUAGE C 8255 - Okti Nur Yudhanti Kusumaningtyas (JAKSTIK Journal, 2004)
Series of "Basic Design of Intermediary Output With Programmable Pheriferal 8255Interface Using C Language", is a circuit which is composed of a PC, Interface 8255, and aseries of Basic Output modules that are interconnected with one another. In 8255 PPI servesto bridge between the computer with the Basic Output circuit. This circuit is useful fordisplaying the output in the form on the LED display.